Numerical Analysis of Deformation and Mechanical Characteristics of Circular Suspended Footing Diaphragm Wall with Deep Tunnel - Zhang, Danqing; Ding, Yushu; Jiang, Kefei; Wang, Bo; Li, Ning (Scientific Journal of Technology, 2025)
Research on circular suspended footing diaphragm walls in "soil-rock combination" strata remains underdeveloped. Understanding deformation and internal force variations during foundation pit excavation is crucial for mitigating safety risks during construction and operation. Based on a circular shaft pit in a water diversion project, this study employs 3D numerical simulations to analyze surface settlement, maximum pit bottom rebound, diaphragm wall deformation ,and internal forces under varying rock-socketed depths. Results indicate: (1) Excavation impacts surface settlement within 0.44H (H is the pit depth). The maximum rebound at the pit bottom in soft soil is significantly greater than that in rock. (2) Diaphragm wall horizontal deformation forms vary as "M," "bow," or "cantilever" with different embedded depths. (3) Large horizontal deformation, bending moments, and shear forces occur at the soil-rock interface and in weak rock strata. (4) Tunnel excavation minimally affects surface settlement and bottom rebound, while increasing maximum wall horizontal deformation by 0.35%–0.55%. However, wall removal in the tunnel area substantially impacts axial bending moments and shear forces. The research results can provide a reference for the design of retaining structure of similar soil rock combined foundation pit.